Clinical significance of interleukin-18 in the course of burn injured children - Efstratiou,F.; Tzortzis,A.S.; Salakos,C.; Kroupis, C.; Dimopoulou, A.; Vrigkou,H.; Papakonstantinou,D.; Zavras,N. (Minerva Pediatr.(Torino), 2022)
BACKGROUND: Burn injury (BI) is one of the most serious causes of morbidity and mortality in the pediatric population. BI triggers an initial stage of hyperinflammation, followed by hypersecretion of both pro- and anti-inflammatory cytokines. IL- 18 is a vital pro-inflammatory cytokine, the effect of which has been investigated not only in animal models but also in adult patients. No study has yet examined the association of serum IL- 18 levels and the clinical significance in the course of pediatric BI. METHODS: We conducted a prospective study including all children with burn injuries who were hospitalized from December 2015 to December 2018 in a tertiary Children's Hospital. RESULTS: A total of 55 children with BI were included. In the present study, we found a strong positive correlation between total body surface area (TBSA) and the levels of IL-18 at admission and on the third day postburn, respectively. The WBC count, the number of lymphocytes and the CRP levels at admission revealed a strong, positive correlation with IL-18 levels. The correlation between IL-18 levels at admission and the length of stay (LOS) was moderate. CONCLUSIONS: This study has shown that the levels of IL-18 collected at admission correlate positively with the extent of TBSA and inflammatory indices in pediatric patients. Moreover, IL-18 levels at admission may not be the most accurate prognostic factor regarding the LOS. However, further research is needed in order to establish more accurate predictive factors for the outcome of BIs in pediatric patients
IS - 2724-5780 (Electronic) IS - 2724-5780 (Linking) LA - eng PT - Journal Article SB - IM